Negotiations of a Homosexual Identity Among Openly-Gay Filipino Santero Community and its Resultant Contradictions in the Culture of Pagsasanto - Quintos, Mark Anthony M.; Piamonte, Samuel Brando (Silliman Journal, 2023)
This research was conducted with the aim of looking into the curious prevalence of Filipinos who identify as gays in the Santero community and how they negotiate their homosexual identity with a form of devotion in a religious idea system that generally does not favor homosexuality. Through a combination of interviews with openly-gay santeros and a series of unobtrusive observations of the online Santero community in three Facebook groups, the study was able to identify three important contradictions in the aforesaid community. These are contradictions in (1) the interactions within the Santero community, (2) the meanings ascribed to the practice, and (3) the norms on the presentation of the Imahes. This paper takes inspiration from extant sociological knowledge on the management of deviant identities and argues that these contradictions are present in the Santero community due to the fact that the Philippine society merely accommodates the deviant identity of gay santeros by obscuring the “sin” of their gayness with the “divinity” of their Santero devotion.